A Phonological Analysis of the Pronunciation of the Rhotic Sound in Word-Final Positions in Joko Widodo’s English Speech at Ecosperity Week 2023 - Gea Amelia; Andang Saehu; Ice Sariyati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study analyzes the realization of the /r/sound in word-final position in President Joko Widodo's English speech at Ecosperity Week 2023 to identify the phonological patterns of Indonesian speakers' interlanguage in the context of international communication. The study employs a descriptive qualitative approach. Data were collected through non-participant observation of audio-visual speech documents and analyzed using phonetic transcription based on the International Phonetic Alphabet (IPA), classification of rhotic and non-rhotic patterns, and interpretation grounded in interlanguage theory. The results indicate that the realization of /r/ in word-final positions is variable but dominated by rhotic patterns, reflecting the strong phonological transfer from Indonesian as the first language. The /r/sound tends to be retained in high-lexical-load words, while non-rhotic variations, such as glottal substitution and deletion, emerge in specific contexts due to articulatory reduction and prosodic stress. These findings indicate that Joko Widodo's English pronunciation does not fully adhere to native speaker norms but rather represents a dynamic interlanguage phonological system through the interaction between L1 transfer and the phonological demands of English. This study confirms that in the context of international speeches, intelligibility is more important than achieving native-like pronunciation as long as the message is effectively conveyed.